The management of the state reserving system in the aspect of the regional economic security supporting - Aleksandr Yefimovich Zemskov; Andrey Fedorovich Shorikov; Natalya Leonidovna Nikulina (Экономика региона, 2011)
This paper reviews the role of the state material reserve system to ensure economic security of the region. A classification of reserves ensuring economic security of the region was elaborated. A scheme of systematic and structural representation of the state material reserve in order to improve the economic security of the region was suggested. Optimization of operational control of the territorial offices, factories, and settlements of custody within the framework of the state material reserve is one of the most effective instruments to enhance the functioning of the whole system. To solve the problem of technological processes optimization of products acquisition and storage in manufacturings, plants and points of consignment storage of the state material reserve, a static economic-mathematical model was developed. The results can be used to develop appropriate computer systems for support of effective management decisions in the system of state of material reserve.